Gender studies in modern linguistics: an analytical and bibliographical review - Olga Dunebabina (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The formation and development of various linguistic trends in linguistics at the turn of the 20th and 21st centuries, which are multidisciplinary and integrative in nature, is a feature of modern linguistics. One of the newest areas of linguistics is linguo-gender studies.